AEROBIC CAPACITY AS DISCRIMINANT OF FEEDING CONSUMPTION AND PHYSICAL APTITUDE (Fiep Bulletin - online, 2014)
The maximum consumption of oxygen is an indicative of aerobic capacity and its estimative constitutes a proper method to analyze nutritional and anthropometric variables of a given subject. This study aimed to evaluate the food intake and body fat distribution of 90 college students of health sciences. Their ages where between 18 and 30 years old, with a maximum intake of oxygen as a differentiation parameter. We determined the indicators, such as: nutritional aspects (macronutrients); anthropometry (body mass index, skinfolds somatorium, waist/hip ratio and trunk/members ratio) and aerobic capacity (maximum consumption of oxygen). In order to evaluate the food intake, we performed a 24 hours memory based questionnaire together with a questionnaire of feeding frequency. The statistical analysis was done using with: ANOVA, t-student, Scheffé and correlation test. The results indicated significant differences and negative correlation for the maximum consumption of oxygen and skinfolds somatorium, concluding that, when there is a higher aerobic capacity, there is a better body fat distribution proportional too. There was also a significant difference for: skinfolds at trunk, waist circumference and waist/hip ratio, predictors of health risks, due to fat accumulation at the central region of the body. We also noticed increased protein intake and regularity at three meals. We noticed a lack of specialized orientation, food intake that does not answer to recommendations and a need for routine physical exercise in order to improve health and quality of life.
Keywords: food intake; body fat distribution; aerobic capacity